2003
DOI: 10.1200/jco.2003.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Whole Body 18FDG-PET and the Response of Esophageal Cancer to Induction Therapy: Results of a Prospective Trial

Abstract: Compared with conventional imaging, PET detects additional sites of metastatic disease at initial evaluation. After induction therapy, PET did not add to the estimation of loco-regional resectability and did not detect new distant metastases. However, changes in [18F]FDG PET may predict disease-free and overall survival after induction therapy and resection in patients with esophageal cancer. Further evaluation in larger trials is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
158
2
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 311 publications
(173 citation statements)
references
References 22 publications
6
158
2
7
Order By: Relevance
“…In our study, we found no significant difference between responders and nonresponders with respect to CT-PET findings at completion of neoadjuvant therapy and before planned surgery. These findings are at variance with reports from previous studies, in which investigators have shown that pathologic responders can be differentiated from nonresponders based on the absolute and percentage decrease in FDG uptake between baseline and completion of neoadjuvant therapy (with ''optimal'' thresholds ranging between 35% and 60%) [14][15][16][18][19][20] or on the degree of residual metabolic activity within the primary tumor after completion of treatment. 12,13,17 It is important to note that in all of these previous reports, criteria for determining therapeutic response based on FDG-PET findings were calculated retrospectively based on re- ceiver operating characteristics (ROC) acquired from the study itself, and have varied from investigator to investigator.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In our study, we found no significant difference between responders and nonresponders with respect to CT-PET findings at completion of neoadjuvant therapy and before planned surgery. These findings are at variance with reports from previous studies, in which investigators have shown that pathologic responders can be differentiated from nonresponders based on the absolute and percentage decrease in FDG uptake between baseline and completion of neoadjuvant therapy (with ''optimal'' thresholds ranging between 35% and 60%) [14][15][16][18][19][20] or on the degree of residual metabolic activity within the primary tumor after completion of treatment. 12,13,17 It is important to note that in all of these previous reports, criteria for determining therapeutic response based on FDG-PET findings were calculated retrospectively based on re- ceiver operating characteristics (ROC) acquired from the study itself, and have varied from investigator to investigator.…”
Section: Discussioncontrasting
confidence: 55%
“…[12][13][14][15][16][17][18][19][20][21][22] Conversely, studies have shown that persistent FDG uptake at the site of the primary tumor after neoadjuvant therapy correlates both with a lack of pathological response to chemoradiotherapy and with a worse clinical outcome, implying that nonsurgical management is indicated for these patients. [12][13][14][15][16]19,20 However, there have only been a limited number of such studies and uncertainty remains over the clinical utility of computed tomography PET (CT-PET), particularly with respect to the optimal timing of performing CT-PET, its specificity for differentiating between residual tumor and therapy-induced inflammation, and the detection of distant metastases after neoadjuvant therapy. 23,24 The aim of this study was to report our clinical experience with CT-PET for detecting distant metastases and in evaluating the therapeutic response of the primary tumor to neoadjuvant therapy in patients with locally advanced potentially resectable esophageal carcinoma.…”
mentioning
confidence: 99%
“…[29][30][31][32] Similar to findings for other cancers, decreases in FDG uptake between 50% and 60% from baseline indicated clinically significant treatment responses. 33,34 Early in treatment, responses also have been identified in patients who have locally advanced disease. 35 Recently, in esophageal cancer, treatment protocols designed to select responders have been initiated.…”
Section: Gastrointestinal Cancersmentioning
confidence: 99%
“…A series of EC patients scanned with FDG-PET before and after induction chemotherapy showed a doubling in two-year disease-free survival when the SUVmax declined by greater than 60% [16]. Because cellular uptake of FLT is a more specific marker for proliferation than FDG, it has theoretical advantages over FDG-PET.…”
Section: Introductionmentioning
confidence: 99%